1998
DOI: 10.1557/proc-554-161
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Electrochemical Behavior of Zr-Al-Cu-Ni Bulk Metallic Glass

Abstract: The passivation behavior of bulk glassy Zr 55 Al 1 0Cu 3 oNi 5 alloy samples in weakly alkaline sulphate solution (pH = 8) is investigated in comparison to the arc-melted crystalline alloy, to the main alloying component zirconium and to aluminium. Results of potentiodynamic and potentiostatic polarization measurements reveal the formation of a stable passivating surface film on the glassy alloy grown by a high-field mechanism. Auger electron spectroscopic investigations of anodized sample surfaces show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In contrast, most, if not all, of the studies of BMG electrochemical behavior have found that amorphous alloys from many different systems are susceptible to localized corrosion. In many of these cases, the sources of pit initiation were determined to be non-ideal BMG castings that contained dispersions of inhomogeneities such as oxides or crystalline inclusions in amorphous matrices, which are commonly formed during the casting process through heterogeneous nucleation at oxygen impurities [51,[53][54][55][56]. Defects in the passive film due to these inhomogeneities serve as active sites for chloride-ion attack and result in penetration of the passive film.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most, if not all, of the studies of BMG electrochemical behavior have found that amorphous alloys from many different systems are susceptible to localized corrosion. In many of these cases, the sources of pit initiation were determined to be non-ideal BMG castings that contained dispersions of inhomogeneities such as oxides or crystalline inclusions in amorphous matrices, which are commonly formed during the casting process through heterogeneous nucleation at oxygen impurities [51,[53][54][55][56]. Defects in the passive film due to these inhomogeneities serve as active sites for chloride-ion attack and result in penetration of the passive film.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to understand the corrosion behavior of investigated alloys in HNO 3 in terms of the differences in the nature of the anodic oxide films formed on surfaces of these alloys as reported in the literature [7,10,11,[17][18][19][20][21][22]. The anodic oxide films on amorphous Zr 67 Ni 33 in 1 N HCl, 1 N HNO 3 and 1 N H 2 SO 4 [7] and on amorphous Ti 50 Cu 50 [17] have been shown to consist of ZrO 2 /Zr(OH) 2 and TiO 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The anodic oxide films on amorphous Zr 67 Ni 33 in 1 N HCl, 1 N HNO 3 and 1 N H 2 SO 4 [7] and on amorphous Ti 50 Cu 50 [17] have been shown to consist of ZrO 2 /Zr(OH) 2 and TiO 2 , respectively. On the other hand it has been reported that the anodic oxide film formed on the bulk amorphous alloy Zr 65 Cu 17.5 Ni 10 Al 7.5 in phosphate-buffered solution [10] and on Zr 55 Al 10 Cu 30 Ni 5 in 0.1 M Na 2 SO 4 [11,18] are complex oxide films consisting of ZrO 2 as major oxide in addition to the other alloying elements Al, Cu and Ni. It was shown by Gebert et al [18] that the complex anodic oxide film formed on amorphous Zr 55 Al 10 Cu 30 Ni 5 in 0.1 M Na 2 SO 4 has poor protective quality than the film formed on pure Zr in the same aqueous medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations